An Interpretation of Hemingway’s The Sea Change from the Perspective of Queer Theory - Fang, Jiamin (Transactions on Social Science, Education and Humanities Research, 2023)
Queer theory, an emerging perspective in literary criticism, provides a distinctive approach to reinterpreting classic literary works. This paper examines Ernest Hemingway’s short story The Sea Change from the perspective of queer theory. The female protagonist is perceived as a “queer” figure by her male lover, the bartender, and the society. The derogatory labeling of the woman as “queer” presents a dilemma for both characters. Through an exploration of identity conflicts, the study reveals contrasting reactions from the female protagonist, who exhibits bravery, determination, and a rebellious spirit, and the male character, who struggles without finding resolution. By analyzing The Sea Change in conjunction with Hemingway’s other works and his personal experiences, the author suggests that features of homophobia and the portrayal of female masculinity can be observed in his depictions of gender roles, which to some extent restrict his comprehensive exploration of queerness in his writing. This research expands the scholarly scope by examining one of Hemingway’s less-explored short stories from an unconventional perspective, shedding new lights on its themes and implications while addressing non-mainstream sexual orientations. It also highlights the significance of applying queer theory to literary criticism and broadens interpretive possibilities and enriches scholarly discussions surrounding Hemingway’s work.